Right Atrium Tumor Extension Through the Inferior Vena Cava. Considerations About Nine Cases Operated Under Cardiopulmonary Bypass - Fernando Chaud (Brazilian Journal of Cardiovascular Surgery)
Abstract Introduction: Adrenocortical and renal cell carcinomas rarely invade the right atrium (RA). These neoplasms need surgical treatment, are very aggressive and have poor prognostic and surgical outcomes. Case series: We present a retrospective cohort of nine cases of RA invasion through the inferior vena cava (four adrenocortical carcinomas and five renal cell carcinomas). Over 13 years (2002-2014), nine patients were operated in collaboration with the team of urologists. Surgery was possible in all patients with different degrees of technical difficulty. All patients were operated considering the imaging examinations with the aid of CPB. In all reported cases (renal or suprarenal), the decision to use CPB with deep hypothermic circulatory arrest (DHCA) on surgical strategy was decided by the team of urological and cardiac surgeons. Conclusion: Data retrospectively collected from patients of public hospitals reaffirm: 1) Low incidence with small published series; 2) The selected cases did not represent the whole historical casuistry of the hospital, since they were selected after the adoption of electronic documentation; 3) Demographic data and references reported in the literature were presented as tables to avoid wordiness; 4) The series highlights the propensity to invade the venous system; 5) Possible surgical treatment with the aid of CPB in collaboration with the urology team; 6) CPB with DHCA is a safe and reliable option; 7) Poor prognosis with disappointing late results, even considering the adverse effects of CPB on cancer prognosis are expected but not confirmed.